Differences in the secretory activity of the atypical adenomatous hyperplasia and low-grade prostatic adenocarcinoma - (:unkn) unknown (My University, 2008)
Atypical adenomatous hyperplasia (AAH) is a small, glandular proliferation that has histological similarities to Gleason grade 1 and 2 prostatic adenocarcinoma (PACG 1, 2). There are no distinct histomorphological criteria distinguishing these two lesions from each other and other small glandular proliferations. It is necessary to defne histological criteria, as treatment approaches are different for these lesions.OBJECTIVES:This study's aim was to evaluate the differences in the secretory properties of AAH and PACG 1, 2. We searched for intraluminal crystalloids, corpora amylacea, mucin, and eosinophilic material.SUBJECTS AND METHODS:105 totally embedded radical prostatectomy specimens containing 11 AAH (22 foci) and 15 PACG 1, 2 (22 foci) lesions were evaluated. Basal cell specifc antikeratin was applied. We accepted that PACG 1, 2 lesions do not contain basal cells, and we grouped lesions as AAH and PACG 1, 2 based on this opinion. The luminal contents were evaluated by PASAB2, 5 and PTAH. RESULTS We found differences between the AAH and PACG 1, 2 lesions for some parameters, including crystalloids, corpora amylacea, and mucin. We found similar properties between the two lesions for eosinophilic material. CONCLUSION In a difficult case, evaluation of the luminal content features may be helpful, but the diagnosis must be supported by immunohistochemistry. © 2008 UroToday International Journal.
Keywords: Adenosis; Crystalloids; Low-grade cancer; Prostate; Small glandular proliferations